FRASA ADJEKTIVAL DALAM CERPEN PILIHAN KOMPAS 2013 KLUB SOLIDARITAS SUAMI HILANG - Siti Marfungah; Mukhlish Mukhlish (Universitas Sarjanawiyata Tamansiswa, 2019)
This research aimed at (1) describing the kinds of adjective phrase in Cerpen Pilihan Kompas 2013 Klub Solidaritas Suami Hilang, (2) describing the categories of attribute filler words in the adjective phrase in Cerpen Pilihan Kompas 2013 Klub Solidaritas Suami Hilang, (3) explaining the structure of adjective phrase in Cerpen Pilihan Kompas 2013 Klub Solidaritas Suami Hilang, and (4) explaining the syntactic function of adjective phrase in Cerpen Pilihan Kompas 2013 Klub Solidaritas Suami Hilang. This research was classified as a descriptive qualitative research. This research data is a sentence that contains an adjective phrase in Cerpen Pilihan Kompas 2013 Klub Solidaritas Suami Hilang. The data source of this research is Cerpen Pilihan Kompas 2013 Klub Solidaritas Suami Hilang which contains 23 short stories. The methods and techniques used during the data collection process were the methods of referring to the skillful dan free listening technique dan note it. The data analysis method and technique used is the agih with techniques for direct elements, slipping techniques, reverse techniques, expanded techniques, and constituent sentence analysis techniques. The method of presenting the results of data analysis is done with informal presentation methods. The results of this research are as follows. (1) the classified of adjective phrase based on the core consistent of (a) adjectival attributive phrase and (b) coordinative adjectival phrase. Filler word categories adjectival phrase attributes consist of verbs, adverbs, nouns, pronouns, and adjectives. The adjectival phrase structure consist of (a) FAdj= (±Adv1 (. . .±Advn)) +Adj (±Adv), (b) FAdj= (±Adv) +Adj , (c) FAdj= (±Adv) ±V (±Adv) +Adj (±Adv), dan (d) FAdj= (±Adv) +Adj1 (. . .+Adjn) ±Konj (±Adv) +Adj (±Adv). The syntactic function of the adjectival phrase consists of subject, predicate, complement, and description